Utilizing Plastic Fabric Waste Through Ecobrick-Based Artwork In Mekarsari Village: Pemanfaatan Limbah Plastik dan Limbah Kain Melalui Ecobrick Sebagai Karya Seni di Desa Mekarsari - Eka Yuli Astuti; Emir Ardi Winata; Fauzan Ramadhani; Muhammad Rizki; Encep Rohmanudin; Refi Mariska (Room of Civil Society Development, 2026)
Plastic and fabric waste are environmental problems faced by the Mekarsari Village community, characterized by limited final disposal facilities and the practice of burning waste and disposing of it into the river. This community service activity aimed to encourage community participation in managing plastic and fabric waste through an ecobrick-based program. The activity was carried out using a Participatory Action Research (PAR) approach consisting of planning, implementation, monitoring, and reflection stages by involving the community, curtain MSMEs as contributors of fabric waste, and village government officials. Data were collected through participatory observation, documentation, questionnaires, and informal interviews. The results showed community participation in collecting and processing plastic and fabric waste into ecobricks. The main achievement of this activity was an installation artwork bearing the village name, composed of 470 ecobrick bottles and placed in front of the Mekarsari Village Office as an educational medium. This activity indicates that a participatory ecobrick-based approach can be an alternative strategy for strengthening community awareness and participation in waste management.